Modeling the impact of mitigation options on abatement of methane emission from livestock - Misra, Arvind Kumar Kumar; Verma, Maitri (Nonlinear Analysis: Modelling and Control, 2017)
Mitigation of methane emission from livestock sector is crucial to combat the menace of global warming. In the present paper, a nonlinear mathematical model is proposed to investigate the impact of mitigation options, for curtailing livestock methane emission, on the reduction of atmospheric concentration of methane. In modeling process, it is assumed that the mitigation options are applied at a rate proportion to the livestock population. The conditions for reduction and stabilization of atmospheric methane have been obtained. Numerical simulation has been performed to verify the analytical findings by taking the secondary data of atmospheric concentration of methane, human and livestock populations. Sensitivity analysis is carried out to explore the impact of the key parameters of the model system.